2009
DOI: 10.5424/sjar/2009073-445
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous wheat-Aegilops biuncialis, Ae. geniculata and Ae. triuncialis amphiploid production, a potential way of gene transference

Abstract: Some F1 hybrid plants between three species of the Aegilops genus and different hexaploid wheat Triticum aestivum cultivars show certain self-fertility, with averages of F1 hybrids bearing F2 seeds of 8.17%, 5.12% and 48.14% for Aegilops biuncialis, Aegilops geniculata and Aegilops triuncialis respectively. In the Ae. triuncialis-wheat combination with ";Astral" wheat cultivar, the fertility was higher than that found in the other combinations. All the F2 seeds studied were spontaneous amphiploids (2n=10x=70).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…durum, 2n = 49 = 28, AABB), triticale (9Triticosecale, AABBRR) and some forage species. Various amphidiploids have been spontaneously produced within this tribe by the formation and union of unreduced gametes (Maan and Sasakuma 1977;Islam and Shepherd 1980;Blanco et al 1983;Xu and Dong 1992;Li and Liu 1993;David et al 2004;Tiwari et al 2008;Loureiro et al 2009). Common wheat originates from spontaneous hybridization of T. turgidum and Ae.…”
Section: Introductionmentioning
confidence: 97%
“…durum, 2n = 49 = 28, AABB), triticale (9Triticosecale, AABBRR) and some forage species. Various amphidiploids have been spontaneously produced within this tribe by the formation and union of unreduced gametes (Maan and Sasakuma 1977;Islam and Shepherd 1980;Blanco et al 1983;Xu and Dong 1992;Li and Liu 1993;David et al 2004;Tiwari et al 2008;Loureiro et al 2009). Common wheat originates from spontaneous hybridization of T. turgidum and Ae.…”
Section: Introductionmentioning
confidence: 97%
“…However, the introgression of genes depends not only on the F 1 hybrid formation in the field, but also on the viability and fertility of the hybrids and their successive generations and on the persistence of introgressed genes. Hybrids between Aegilops species and wheat often are considered self‐sterile; however, F 2 seeds, commonly formed by spontaneous amphiploid production, 21 can be found at rates of 0.08% (0.05–0.16) and 1.82% (0.17–5.44) seeds per spikelet for A. geniculata – and A. triuncialis –wheat hybrids, respectively. Seed‐set was higher when F 1 hybrids were backcrossed with wheat, 22 with an average of 2.87% (0–9.26) for A. geniculata under experimental field conditions, 39 whereas fertility increased from F 1 to the BC 1 and F 2 generations of hybrid progenies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…22 These backcrosses, recombination and spontaneous amphiploidy, can result in wheat-Aegilops gene introgression. [1][2][3][4]21,22,40 Different studies conducted in the United States on the hybridization between wheat and A. cylindrica (CCDD), also in the context of risk assessment of GM herbicide-tolerant wheat, have demonstrated that hybrids and backcross derivatives can be formed under field conditions between both species. 25,26 The selection pressure from the herbicide could give a selective advantage to the hybrids and/or backcrosses that carry the resistance gene from wheat, a situation that may allow gene flow between these two species and the introgression of the wheat gene conferring the selective advantage into the weedy population.…”
Section: Discussionmentioning
confidence: 99%
“…triuncialis has been reported. The risk assessment of GM wheat cultivars needs to evaluate the importance of amphiploids as a bridge for transgene introgression and for gene escape to the wild (Loureiro et al, 2009).…”
Section: Wheat (Triticum Aestivum) and Other Cerealsmentioning
confidence: 99%